Examining the Causes and Prevention of Book Losses in Academic Libraries - Abid Hussain, Muhammad Imbrahim (IJoLIS, 2024)
Purpose: This article is an attempt to examine the current situation of book losses/theft, their causes, and remedies that have been takne by academic libraries in Pakisan